Strategi Psikologis Lansia Kelurahan Oeba dalam Menghadapi Bencana - Putra, Theodorus Vigilius Dwi; Celline Loainak, Diva; Dubu, Rima Gracia; Rihi, Syalum Wieska; Ledo, Melani Claudia; Leo, Fiki Rehi; Pello, Shela (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Indonesia is highly prone to disasters due to its location between three active tectonic plates: Indo-Australia, Eurasia, and Pacific. Frequent disasters, such as floods, earthquakes, and extreme weather, have a significant impact, especially on vulnerable groups like the elderly. The elderly often experience psychosocial impacts like anxiety and stress during disasters, thus requiring appropriate psychosocial support. Objective: This community service aimed to provide psychosocial support to the elderly at Posyandu Lansia Latulip 4, Oeba Village, in facing disasters through the Progressive Muscle Relaxation (PMR) technique. Method: The methods used in this activity included lectures and direct practice of PMR to help reduce anxiety and increase the preparedness of the elderly in facing disasters. The instruments used were pre-tests and post-tests to measure the effectiveness of the activity. Result: The results of this activity showed a significant increase in disaster preparedness knowledge among the elderly, with understanding levels rising from 66.25% to 92.5% after the activity. Conclusion: The psychosocial education provided through the PMR method was effective in improving disaster preparedness and calming the elderly in facing disaster situations.